2007
DOI: 10.1016/j.jcis.2007.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of clay-supported titania photocatalysts

Abstract: This study examines the use of laponite, a synthetic smectite, which forms exfoliated silicate layers when dispersed in water, as an inorganic support for titania nanocrystals. Titania nanocrystals are prepared prior to addition to the clay dispersion, by a sol-gel synthesis incorporating a microwave hydrothermal step. The characteristics of the resultant structure such as titania phase, crystallite size and particulate size are examined via X-Ray Diffraction (XRD), Transmission Electron Spectroscopy (TEM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 42 publications
1
28
0
2
Order By: Relevance
“…clearly shows the presence of discrete anatase particles in TiO 2 /NCC structure [23]. The two characteristic peaks at 1554 and 1492 cm −1 in P(Py-co-An)-TiO 2 /NCC correspond to the frequencies of aromatic ring in PAn, which are stretching of quinine ring and benzene rings, respectively [24].…”
Section: Ftir Analysismentioning
confidence: 92%
“…clearly shows the presence of discrete anatase particles in TiO 2 /NCC structure [23]. The two characteristic peaks at 1554 and 1492 cm −1 in P(Py-co-An)-TiO 2 /NCC correspond to the frequencies of aromatic ring in PAn, which are stretching of quinine ring and benzene rings, respectively [24].…”
Section: Ftir Analysismentioning
confidence: 92%
“…showed that the samples prepared with different hydrothermal treatment temperatures exhibited the following trend in photoactivity: Ti-L40-180 > Ti-L40-140 > Ti-L40-80 [16]. Titania is commonly reported to exhibit greatest activity with samples of smaller crystallite size, however, in this case, the larger samples produced by more severe hydrothermal treatment are the most photoactive.…”
Section: Effect Of Hydrothermal Treatment Temperaturementioning
confidence: 97%
“…The samples are ranked by the degree of degradation achieved over 90 minutes of irradiation by UV light, and are as follows: Ti-L40-180 > Ti-L30-180 > Ti-L10-180 > Ti-L20-180 [16]. The Ti concentration was therefore found to have some effect on the photocatalytic activity of the sample, however there is no direct relationship present.…”
Section: Effect Of Titania Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Three main reactions that occur during the sol-gel process are hydrolysis, alcohol condensation and water condensation. The reaction is as follows [27]…”
Section: Experimental Procedures a Powder Synthesismentioning
confidence: 99%